Comparing edge and fragmentation effects within seagrass communities: A meta‐analysis. Issue 3 (28th January 2022) - Yarnall, Amy H.; Byers, James E.; Yeager, Lauren A.; Fodrie, F. Joel
Abstract: Examining community responses to habitat configuration across scales informs basic and applied models of ecosystem function. Responses to patch‐scale edge effects (i.e., ecological differences between patch edges and interiors) are hypothesized to underpin the effects of landscape‐scale fragmentation (i.e., mosaics of multipatch habitat and matrix). Conceptually, this appears justifiable because fragmented habitats typically have a greater proportion of edge than continuous habitats. To critically inspect whether patch‐scale edge effects translate consistently (i.e., scale up) into patterns observed in fragmented landscapes, we conducted a meta‐analysis on community relationships in seagrass ecosystems to synthesize evidence of edge and fragmentation effects on shoot density, faunal densities, and predation rates. We determined effect sizes by calculating log response ratios for responses within patch edges versus interiors to quantify edge effects, and fragmented versus continuous landscapes to quantify fragmentation effects. We found that both edge and fragmentation effects reduced seagrass shoot densities, although the effect of edge was statistically stronger. By contrast, fauna often exhibited higher densities in patch edges, while fragmentation responses varied directionally across taxa. Fish densities trended higher in patch edges and fragmented landscapes. Benthic fishes responded more positively than benthopelagic fishes to edge effects, although neither guild strongly responded to fragmentation. Invertebrate densities increased in patch edges and trended lower in fragmented landscapes; however, these were small effect sizes due to the offsetting responses of two dominant epifaunal guilds: decapods and smaller crustaceans. Edge and fragmentation affected predation similarly, with prey survival trending lower in patch edges and fragmented landscapes. Overall, several similarities suggested that edge effects conform with patterns of community dynamics in fragmented seagrass. However, across all metrics except fish densities, variability in fragmentation effects was twice that of edge effects. Variance patterns combined with generally stronger responses to edge than fragmentation, warrant caution in unilaterally "scaling‐up" edge effects to describe fragmentation effects. Alternatively, fragmentation includes additional factors (e.g., matrix effects, patch number, mean patch size, isolation) that may enhance or offset edge effects. Fragmentation and increased edge are syndromes of habitat degradation, therefore this analysis informs mechanistic models of community change in altered terrestrial and marine systems.